Curso Autoformativo de Português para Intercâmbio (CAPI): didactic materials based on the notions of language use and discourse genre - Timboni, Kétina Allen da Silva; Rupert, Andrea de Araújo; Schlatter, Margarete (BELT - Brazilian English Language Teaching Journal, 2019)
Curso Autoformativo de Português para Intercâmbio (CAPI) is a MOOC (Massive Open Online Course) that aims to prepare students for academic exchange programs. The didactic materials of CAPI are being designed based on a perspective of language use (Clark, 2000) and discourse genres (Bakhtin, 2011). This paper analyzes the course contents in order to examine how this theoretical construct was put into practice in the selection of themes and texts and in the design of the pedagogical tasks. The materials are coherent with the theoretical perspective in that they foster the learning of Portuguese in use and to use through the interaction with oral and written texts in social practices in which students might participate in the university and the city of destination, thus preparing them for their stay. The addition of explicit reflection on possible implications of interlocutors’ relations to the use of linguistic-discursive and cultural repertoires is suggested.